Boy : Tales of childhood - Dahl, Roald (London : Penguin Books, 1984)
Presents humorous anecdotes from the author's childhood which includes summer vacations in Norway and an English boarding school.
Keywords: Dahl, Roald -- Childhood and youth -- Juvenile literature; Dahl, Roald; Authors, English -- 20th century -- Biography -- Juvenile literature; Authors, English; Great Britain -- Social life and customs -- Juvenile literature